The impact of robots on labour market transitions in Europe - Ronald Bachmann; Myrielle Gonschor; Piotr Lewandowski; Karol Mandoń (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
We study the effects of robot exposure on worker flows in 16 European countries. Overall, we find small negative effects on job separations and small positive effects on job findings. Labour costs are shown to be a major driver of cross-country differences: the effects of robot exposure are generally larger in absolute terms in countries with low or average levels of labour costs than in countries with high levels of labour costs. These effects were particularly pronounced for workers in occupations intensive in routine manual or routine cognitive tasks, but were insignificant in occupations intensive in non-routine cognitive tasks. For young and old workers in countries with lower labour costs, robot exposure had a beneficial effect on transitions. Our results imply that robot adoption increased employment and reduced unemployment most in the European countries with low or average levels of labour costs.
Keywords: J24; O33; J23; 330; robots; technological change; tasks; labour market effects; Europe